Optimization Consumer Cost of Food Industry with Perishable Characteristic. (July 2019) - Rizkya, I; Nasution, A A; Syahputri, K; Sari, R M; Siregar, I; Erwin,
Abstract: Food product has time limit usage, namely expired date. The time limit for product usage (expiration) is one of the factors affects the number of inventory and total inventory costs. Expiration factors are important in planning because they do not only affect the costs to the company but also includes product safety issues when consumed. Products are close to expirate date will decrease in sales value until they have no value at all. Expiration factors must be considered in determining the optimal number of inventory capable to minimize the number of expired products and minimize the number of lost sales. This paper describes the Q method approach to obtain optimal order size capable to minimize expired products and lost sales to the consumer. Q model approach is used for product inventory models are undurable. The product inventory model for undurable product calculates the inventory not only minimize due to demand but also due to damage. The study was conducted to minimize the total costs by consumers cost and considering expired factors and lost sales. The results obtained in this article shows that the total cost of consumers is IDR 3.430.756/month and acceptance frequency is 22 times per month.